Penguatan Pemahaman Fikih Thaharah melalui Edukasi Praktis: Studi Pengabdian di Desa Nglayang Ponorogo - Candra Febrilyantri; Arina Nisaal Khasanah; Diva Tria Amanda; Muhammad Ridwan Asyrofi; Najmatuzzahiroh Sholehah (Jurnal Pengabdian Masyarakat Universitas Darul Ulum, 2025)
Nglayang Village is one of the villages with a majority of Muslim population and has a strong religious tradition. Although there is a strong religious tradition, the observation results actually indicate that there are issues related to the practice of purification (thaharah) that are not in accordance with sharia rules. Some residents still apply the wrong way of purification, both related to small and large hadas, which can potentially affect the validity of prayer. The implementation team carried out community service activities using the Asset Based Community Development (ABCD) method through the fiqh taharah literacy program. This activity involves religious leaders, young people, and the wider community through training, discussions, and simulations of purification practices in accordance with Islamic teachings. The results of the activities show an increase in people's knowledge and skills in carrying out taharah, as well as increasing awareness of the importance of correct purification for the validity of worship and the preservation of spiritual values in daily life